Arbitrary and Incorrigible Allocations: A Comment. - Thomas, Arthur L. (The Accounting Review, 1978)
Abstract Enough of this "glory," as Humpty Dumpty might call it. Eckel has served for years on the Canadian analogue to the APB. This makes it all the more gratifying that, despite our differences, we agree the main points: Financial accounting's allocation theory is a wretched mess, and things won't improve until we accountants radically revise our notion of income. A reading of [Kuhn, 1970, pp. 12-22, 47-48, 84, 162-65, 178-79] suggests that such a mess is just what one should expect of a pre-paradigmic19 discipline like financial accounting. If enough accountants of Eckel's professional eminence come to share his recognition of our intellectual crisis, our discipline may someday begin to prosper in the way the physical sciences have. Let's hope that these accountants do, for, as [Thomas, 1974, pp. 156-57] pointed out, this mess is also an ethical one. Meanwhile, to paraphrase the movie ad of a few years back, we can only continue to pray for Pacioli's Baby.